2020
DOI: 10.1002/pol.20200089
|View full text |Cite
|
Sign up to set email alerts
|

Arm‐first star‐polymer synthesis in one‐pot via alkylborane‐initiated RAFT

Abstract: An alkylborane initiated reversible addition-fragmentation chain transfer (AI-RAFT) process was developed for the synthesis of star-polymers using a onepot approach at room-temperature in the presence of oxygen. Linear poly(tertbutyl acrylate) arms were first polymerized using a latent trialkylborane-amine initiator, which generated trialkylborane, in situ, and subsequently radicals after reaction with oxygen. Polymerizations were optimized to maximize monomer conversion (~70-80%) and minimize arm-dispersity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…1b). In addition, the characteristic peak with a chemical shift at 66.13 ppm in the 19 F NMR spectrum was attributed to the fluorine atom in the benzenesulfonyl fluoride fragment (Figure S2, Supporting Information). Furthermore, the characteristic infrared peaks at 1722 and 1658 cm -1 were assigned to the carbonyl bond in the ester and benzophenone groups, respectively (Figure S3, Supporting Information).…”
Section: Synthesis Of Bp-fsbcmentioning
confidence: 99%
See 3 more Smart Citations
“…1b). In addition, the characteristic peak with a chemical shift at 66.13 ppm in the 19 F NMR spectrum was attributed to the fluorine atom in the benzenesulfonyl fluoride fragment (Figure S2, Supporting Information). Furthermore, the characteristic infrared peaks at 1722 and 1658 cm -1 were assigned to the carbonyl bond in the ester and benzophenone groups, respectively (Figure S3, Supporting Information).…”
Section: Synthesis Of Bp-fsbcmentioning
confidence: 99%
“…The chemical structure of the synthesized PHEA was also analyzed by 1 [31] and the characteristic chemical shift at 64.46 ppm in the 19 F NMR spectrum was assigned to the fluorine atom in the benzenesulfonyl fluoride group (Figure S6, Supporting Information). These data indicated that the benzophenone and benzenesulfonyl fluoride fragments inherited from the RAFT agent BP-FSBC were preserved at opposite ends of the PHEA chain.…”
Section: Photocontrolled Raft Polymerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been an increased interest in polymer synthesis using boron-containing compounds. [22][23][24][25][26][27][28][29][30][31][32][33][34] One of the benefits of polymerization in the presence of organoboranes is a high rate of initiation at ambient temperature even in the presence of atmospheric oxygen. Chung et al discovered that polymerization of some monomers in the presence of a trialkylborane/atmospheric oxygen system proceeds in a controlled manner due to the dissociation-recombination of active terminal borane fragments.…”
Section: Introductionmentioning
confidence: 99%